Design and development of piston-controlled intake port for 4-stroke engine - Amran, Kaharudin (2008)
In a two stroke engine, piston control the intake port opening and closing that combine the intake and compression stroke in 1800 crank rotation. The operational concept of two stroke engine is applied to the existing four stroke engine cylinder head. The four stroke engine cycle is more fuel-efficient, clean burning and higher engine power output due to higher volumetric efficiency, higher combustion efficiency and low sensitivity to pressure losses in exhaust system. However, the four stroke engine is high manufacturing cost due to more components compared to the two stroke engine. The objective of this work is to study the existing base four stroke engine valvetrain, design and develop piston controlled intake port for the base Modenas engine. The work also describe the concept design process using theoretical calculation and Solidworks software with the animation and basic CFD simulation to indicates the flow pattern and compare to the original design. From the theoretical calculation is observed that, the torque and power increased up to 34.8% and 7.5% compare to the base engine. Flow simulation done at the intake stroke shows that there is improved in flow pattern with more uniform swirl generated but this new cylinder head design did not much different in velocity and pressure flow pattern. The power losses in the valvetrain will be reduce due to less energy output from crankshaft needed to drivethe upper crank arm. Furthermore, the upper piston will provide power during power stroke and instead of building whole new engine, replacing the existing cylinder head with this new cylinder head can significantly reduce cost, time to market and improve existing product reliability.